Local Deformation of the Erythrocyte Membrane Induced by Focused Light Illumination - Wong, Felix (My University, 2005)
A rapid local deformation of the erythrocyte membrane in the shape of an imprint caused by illumination with a focused laser beam in the presence of an external fluorophore has been investigated. This morphological change of the membrane appeared to be the very first observable step of the photohemolysis process which is exploited in photodynamic therapy. I showed that when a laser beam was focused on the erythrocyte membrane, the membrane was pulled toward the inside of the cell, independently of the direction in which the light was traveling. Imprint formation was observed neither on the lipid membrane of giant unilamellar vesicles nor on the membrane of nucleated mammalian cells such as HeLa cells. It shows that the effect is specific to erythrocytes; suggesting that it might be due to the unique structure of the erythrocyte membrane cytoskeleton. Also, I found that the rate of the imprint formation depended on laser input power, fluorophore concentration, and the presence of oxygen scavenger, but that it was independent of pH in the range pH= 6.4 to 7.8. These dependences are exactly the same for photohemolysis and for the imprint formation. By analogy with the photohemolysis process, these observations suggest that the imprint is created via the oxidization of band 3 proteins on the erythrocyte membrane. It supports the hypothesis that band 3 proteins play a pivotal role in the preservation of the erythrocyte shape. Preliminary work also suggests that spectrin is involved in the imprint formation process.
Local Deformation of the Erythrocyte Membrane
Keywords: erythrocyte; light; deformation; illumination